Electronic documents: Reflections on information professionals´ relationships with technology. Part I - Bustelo-Ruesta, Carlota (Anuario ThinkEPI, 2008)
The relationship between information technologies and information professionals is becoming more complex in an environment in which, for the first time, standards and legislation are ahead of implementation and there are many hidden commercial interests. One example is the workshop on open document formats organized by the EU. Confrontation between ODF (ISO 26300) and Microsoft´s attempt to convert Ooxml into an open format through ISO was widely debated, but there was little discussion about practical solutions. Adobe´s strategy, opening its formats when free applications are in use, has proved successful.